PHARMACEUTICAL COMPANIES LEVERAGING DIGITAL CHANNELS TO PROMOTE BRAND AWARENESS AMONGST DOCTORS POST COVID-19 - Devang Shandilya (International Journal of Modern Agriculture, 2020)
The research paper probes into the fact of why the digital channels make for a much better platform for promoting the medical brands. A literature review was conducted on the same to make sure proper level of information is available to the researcher in the first place. It was chosen that interview questions would be used to collect data in this research process. This is because the researcher needs a vast level of information on the topic of the same. The interview questions, with the participant of the research process, would help the researcher gather valuable information about brand awareness.